Pembentukan Karakter Santri Berbasis Pendidikan Pesantren (Studi Kasus Pondok Pesantren Baitun Nur) - Masitoh, Dewi; Nisa, Khoirotun (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
One of the character-building educational institutions is Pondok Pesantren. The words pesantren may often be heard in our ears because there are many pesantren in almost all corners of the country and in particular are very easy to find in the Java region. Usually this pesantren has a leader or caregiver who is usually called a Kyai. The presence of kyai as guardians of integrity, firmness of attitude, character, and ideology of goodness is integrated into the pesantren system, where the firmness of the pesantren and the advice of caregivers are the sources of decision making. Caregivers are magnets for the obedience and submission of the students continuously in the pesantren environment. Pesantren always exist and grow sensibly because they are forged with activities and the surrounding environment that are embedded in the souls of students. The formation of a typical pesantren culture is different from the non-pesantren education system, which includes the values of simplicity, independence, honesty, as well as brotherhood that is still based on the spirit of religion. Pesantren is also an educational institution whose learning system is carried out every day for 24 hours continuously. This pesantren activity from waking up until going to bed aims to shape the character of the students, so that students can be trained in activities that have positive values and discipline. Character building can be integrated into everyday life, both as an intermediary for learning in the classroom or outside the classroom, so that these activities are easier to carry out only in Islamic boarding schools where students can be controlled by a good environment.